Occurrence of Phytophthora cinnamomi in cork oak forests in Italy (Forest Pathology, 2013)
An increasing decline and mortality of cork oak trees have been recently observed in central Italy and Sardinia Island. Following surveys conducted in three declining cork oak forests, a Phytophthora species was consistently isolated from soil samples collected from trees displaying different level of decline. Based on morphological features, growth rates at different temperatures and analysis of DNA sequences of the ITS region, all isolates were identified as Phytophthora cinnamomi Rands. This pathogen caused large brownish lesions on inoculated freshly cut branches of cork oak. It was re-isolated from all infected tissues. These findings represent the first report of P. cinnamomi on cork oak trees in Italy.